Analisis Kepatuhan Warga Muhammadiyah Terhadap Penggunaan Bank Syariah (Studi Kasus Universitas Muhammadiyah Makassar) - Ahmad Azhary Anas; Muhammad Ridwan; Siti Walida Mustamin (Yayasan Al-Afif, 2026)
This study examines the level of compliance of Muhammadiyah members at Universitas Muhammadiyah Makassar in using Islamic banking services and identifies the factors influencing such compliance. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving students and academic community members. The findings indicate that the level of compliance in using Islamic banks remains relatively low, despite the institution’s strong Islamic values. This condition is primarily influenced by limited Islamic financial literacy, misconceptions regarding the differences between Islamic and conventional banks, environmental and social influences, and perceived convenience of conventional banking services. From an Islamic perspective, compliance in financial transactions is closely linked to religious awareness and adherence to Sharia principles. Therefore, strengthening Islamic financial education, enhancing the Islamic campus culture, and fostering collaboration between universities and Islamic banks are essential strategies to improve Sharia banking compliance within Islamic higher education institutions